Pengaruh Pertumbuhan Ekonomi dan Pengangguran terhadap Indeks Pembangunan Manusia di Kabupaten Sampang - Channa Chamdiyah Atsaniyah; Riza Yonisa Kurniawan; Heny Musfidah (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2025)
Human Development Index (HDI) is an important indicator to measure the quality of human development in a region. However, there is still a gap between economic growth and unemployment to HDI in several regions, including Sampang Regency. This study aims to analyze the influence of economic growth and unemployment on HDI in Sampang Regency, East Java during the period 2021 – 2024. This study uses secondary data from the Central Statistics Agency (BPS), and is analyzed using multiple linear regression. The results of the study show that economic growth has a negative value and has no effect on HDI. This shows that the increase in economic growth in Sampang Regency is not automatically followed by an improvement in the quality of human development. The unemployment variable has a negative value and affects HDI, which shows that if unemployment decreases, many of the workforce already have jobs so that they can improve their quality of life which will later increase HDI. Simultaneously, these two variables affect HDI in Sampang Regency. Based on these findings, policies are needed that encourage equitable development, job expansion, and improve the quality of education and health services so that welfare can be felt by all levels of society.